Analysis of recurrent hypoglycemic events. Issue 1 (2nd January 2021) - Ma, Chenchen; Qu, Yongming; Fu, Haoda
ABSTRACT: Hypoglycemia is a major safety concern for diabetic patients. Hypoglycemic events can be modeled based on time to recurrent events or count data. In this article, we evaluated a gamma frailty model with variance estimated by the inverse of observed Fisher information matrix, a gamma frailty model with the sandwich variance estimator, and a piecewise negative binomial regression model. Simulations showed that the sandwich variance estimator performed better when the frailty model is mis-specified, and the piecewise negative binomial regression sometimes fails to converge. All three methods were applied to a dataset from a clinical trial evaluating insulin treatments.